Rancang Bangun Sistem Persediaan Barang PT. Daya Cipta Karya Sempurna - AWALUDDIN, CANDRA KITSI; Edy Supriyanto (Elkom: Jurnal Elektronika dan Komputer, 2023)
Data Processing PT. Daya Cipta Karya Sempurna regarding the entry and exit of goods at PT. Daya Cipta Karya Sempurna still uses a semi-manual system where when the ordered goods arrive, the items will be recorded in the warehouse using Microsoft Excel. Likewise with the items that come out are also recorded in the warehouse using Microsoft Excel. In addition, this information only exists in the warehouse so that when other parts or want to know the inventory of existing goods, other parts cannot access it directly. The section must ask the warehouse to find the state of the desired supply and must wait to get the answer. As a solution to the problems above, it takes an inventory system at PT. Daya Cipta Karya Sempurna Power that can be used to manage goods group data, goods data, user data, incoming goods data and outgoing goods data as well as display reports